PEMETAAN KATEGORI DIMENSI SMART CITY BERDASARKAN RAGAM INOVASI APLIKASI DAN SITUS WEB MANAJEMEN PERKOTAAN DI INDONESIA - Irsyad Adhi Waskita Hutama; Achmad Djunaedi (TATALOKA, 2019)
This research is motivated from the emerging of Smart City (SC) concept which lately has been implemented in Indonesian’s cities such as Jakarta, Bandung, and Surabaya as a mean to tackle city’s problems digitally. The use of Information and Communication Technology (ICT) becomes one of the SC characteristic which transformed into applications and websites. The main purpose of the research is to map the categorization of SC dimension based on the abundance of aplications and web sites for cities management. The explorative and qualitative approach was used as research method involving secondary data collection, categorization scheme, and pairing to Giffinger’s SC dimensions. About 338 SC’s innovation accounted from cities in Indonesia but only 109 registered as applications or websites. From those numbers, we then categorize into 14 typologies of applications/websites based on its methods in tackling urban problems. They are job related information, transport and traffic, education, citizen participation, environmental management, governance, bureaucracy/permission, staffing, health, energy management, disaster mitigation, criminality, entrepreneurship, and culture and tourism. As result, those categorizations are, in fact, more comprehensive than those of Giffinger’s six smart city dimensions by adding two more dimensions namely Smart Energy Management and Smart Disaster Mitigation. Despite the availability of the applications and websites related to them, the implementation is still limited.